2015
DOI: 10.3310/hta19320
|View full text |Cite
|
Sign up to set email alerts
|

Calculating when elective abdominal aortic aneurysm repair improves survival for individual patients: development of the Aneurysm Repair Decision Aid and economic evaluation

Abstract: BackgroundAbdominal aortic aneurysm (AAA) repair aims to prevent premature death from AAA rupture. Elective repair is currently recommended when AAA diameter reaches 5.5 cm (men) and 5.0 cm (women). Applying population-based indications may not be appropriate for individual patient decisions, as the optimal indication is likely to differ between patients based on age and comorbidities.ObjectiveTo develop an Aneurysm Repair Decision Aid (ARDA) to indicate when elective AAA repair optimises survival for individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 122 publications
1
13
0
Order By: Relevance
“…In this illustrative example, we have shown that the current UK threshold guidelines for AAA intervention (a diameter ≥ 5.5 cm) are sensible for patients of older ages, but could perhaps be reduced for younger individuals. These findings are concordant with previous research, which developed a decision aid tool for management of AAA (Grant et al, 2015). However, much uncertainty remains and future work will apply these methods to data collected from multiple studies involving 11,262 men and 178 rupture events (Thompson et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…In this illustrative example, we have shown that the current UK threshold guidelines for AAA intervention (a diameter ≥ 5.5 cm) are sensible for patients of older ages, but could perhaps be reduced for younger individuals. These findings are concordant with previous research, which developed a decision aid tool for management of AAA (Grant et al, 2015). However, much uncertainty remains and future work will apply these methods to data collected from multiple studies involving 11,262 men and 178 rupture events (Thompson et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…First and foremost, factors that might confound the comparison of men and women, such as age, aneurysm diameter, and comorbidities, were inconsistently reported. Operative mortality is known to increase with age, and women appear to develop clinically relevant aneurysms at an older age than men 37, 38. Since prevalence increases rapidly with age, especially in women, 39 this factor is an important consideration.…”
Section: Discussionmentioning
confidence: 99%
“…60 This analysis has also identified important demographic and clinical factors that influence late survival and such factors should be considered in predictive late survival modelling tools and clinical decision making. 35,54 Varying definitions of major co-morbidities, such as cardiac failure and COPD in published studies, markedly hinder the evaluation of the influence of these conditions on outcomes such as long-term survival after AAA repair. The findings from this review highlight the major contribution from these differing definitions to the occurrence of heterogeneity in the various results.…”
Section: Discussionmentioning
confidence: 99%